Pelaksanaan BPJS Ketenagakerjaan terhadap karyawan (Studi di PT. Wonebesco Group Indonesia) - Iskatrinah; Esti Ningrum; Gholibudin Zuhaermanto (Wijayakusuma Law Review, 2024)
The purpose of this research is to determine the procedures and obstacles in implementing the Employment Social Security Administering Agency at PT. Wonebesco Group Indonesia Purwokerto Banyumas Regency. The approach method in this research is normative juridical, namely an approach that uses a legalistic positivistic conception., the data used is primary data through observations and interviews with sources and respondents as main data, secondary data as supporting data in the form of legal materials, research specifications using research Clinical law (Clinical Legal Research) is research to apply law in abstracto to cases in concrete. The data obtained will be analyzed using qualitative analysis methods, namely by observing the data obtained with the provisions and legal principles related to the problem being studied. This research was conducted to answer the procedures and obstacles in the Implementation of the Employment Social Security Administering Agency at PT. Wonebesco Group Indonesia Purwokerto Banyumas Regency. with a positivistic legal conception method. Implementation of BPJS Employment at PT. Wonebesco is in accordance with applicable laws and regulations by applying the percentage of contributions borne by the employer and the workforce. Giving rights to workers who have passed their term of employment or have not received a contract extension to receive assistance and guidance by the company in making claims against BPJS Employment